2017
DOI: 10.1093/scan/nsx016
|View full text |Cite
|
Sign up to set email alerts
|

Empathy for pain motivates actions without altruistic effects: evidence of motor dynamics and brain activity

Abstract: Empathy has been supposed to be a proximate mechanism of altruistic behavior. We investigated whether empathy for pain drives actions without altruistic effects and how such actions modulate neural responses to others’ pain. In two experiments, we asked healthy adults to press a button for no reason when viewing video clips showing faces with pain expressions receiving needle penetration or faces with neutral expressions receiving a cotton swab touch. Experiment 1 found that participants pressed a button with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Contrast analyses also pointed to bilateral occiptotemporal activations that were more likely to be engaged during observed pain, but not direct pain experience. Previous fMRI research have explained these activations for empathic viewing in terms of enhanced visual processing ( Azevedo et al., 2013 ) likely due to augmented salience ( Akitsuki and Decety, 2009 ) or attention ( Han et al., 2017 ) for pain scenes. As with supramarginal activation patterns, such lateral occipitotemporal activations are often reported with minimal or no discussion ( Vachon-Presseau et al., 2012 ; Morelli et al., 2014 ; Seara-Cardoso et al., 2015 ; Enzi et al., 2016 ; Fourie et al., 2017 ; Richins et al., 2019 ), despite often being amongst the strongest research results in terms of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast analyses also pointed to bilateral occiptotemporal activations that were more likely to be engaged during observed pain, but not direct pain experience. Previous fMRI research have explained these activations for empathic viewing in terms of enhanced visual processing ( Azevedo et al., 2013 ) likely due to augmented salience ( Akitsuki and Decety, 2009 ) or attention ( Han et al., 2017 ) for pain scenes. As with supramarginal activation patterns, such lateral occipitotemporal activations are often reported with minimal or no discussion ( Vachon-Presseau et al., 2012 ; Morelli et al., 2014 ; Seara-Cardoso et al., 2015 ; Enzi et al., 2016 ; Fourie et al., 2017 ; Richins et al., 2019 ), despite often being amongst the strongest research results in terms of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of empathy have indicated SMA’s involvement during the observation of emotion 7,11,50 ; this region may represent the motor and behavioural drive component of empathic responding 51 much as it organizes behavioural responses to personally experienced pain. For example, Han and colleagues found that empathy for pain facilitates motor action (the force and velocity of a button press), and that empathic responses in SMA are reduced when engaging in motor activity relative to when passively viewing others’ pain 52 . Our findings further link representations of empathic pain in SMA to increased altruistic motivation and the perception of others’ pain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Morrison et al demonstrated that observing a needle pricking a fingertip facilitates withdrawal and inhibits approach movements (Morrison et al 2007b). Several studies also indicate that observing pain in others elicits a non-specific movement facilitation (Morrison et al 2007a; Han et al 2017; Galang et al 2017; Fabi and Leuthold 2017). In particular, a recent study by Galang and Obhi (2019) has shown that observing needle penetrations into right hand from the egocentric perspective decreased latencies of button presses to go signals carried out with the right hand and this response facilitation was stronger after explicitly instructing observers to empathize with a person in pain.…”
Section: Empathy For Pain and Skeletomotor Activitymentioning
confidence: 99%